Impact of COVID-19 on the national tuberculosis elimination program in uttarakhand, india: a mixed-methods research study - Kirti Garg; Yogesh Bahurupi; Pradeep Aggarwal; Mayank Badola (Elsevier, 2023)
Summary: Background: The COVID-19 pandemic has had adverse effects on tuberculosis (TB) management in high-burden countries. We conducted a qualitative study to assess the impact of COVID-19 on Uttarakhand's TB elimination program. Methods: A mixed-methods study was conducted to assess the impact of COVID-19 on the National Tuberculosis Elimination Program (NTEP) in Uttarakhand, India. We collected secondary data through the NIKSHAY portal from April 1, 2019, to March 31, 2021, interviewed program managers for the qualitative part of the study, and documented changes in some of the program core indicators during the study period. Results: The study showed a decrease in TB case notification, an increase in the proportion of missing cases, and a fall in the treatment success rate of new cases during the ongoing COVID-19 pandemic by 17%, 54%, and 45%, respectively. Content analysis of in-depth interviews showed disruption in TB-care services because of COVID-19. Conclusion: TB care services in Uttarakhand have been impacted by measures taken to curb the spread of COVID-19. Both the quantitative and qualitative aspects of the study showed a serious impact on notification rates, diagnostic services, and treatment outcomes for TB patients. In addition, some negative changes have been observed when documenting program indicators (annual case notifications, success rate, treatment success rate) of the National Tuberculosis Elimination Program (NTEP). It is thus predicted that COVID-19 will undermine the Government of India's goal to eradicate TB by 2025 and will negatively affect the TB Program.